A Cladding-Pumped Device for Modal Gain Equilization Based on Rippled Few Mode Fiber - Lu Dai; Yuanpeng Ding; Hui Zhang; Junjie Qi; Hongyan Shi; Jun Chu; Lei Zhang; Lei Shen; Zhaolong Liao; Shiqi Zhou; Jie Luo (IEEE Photonics Journal)
To achieve mode-division multiplexing (MDM) for long-distance transmission, the development of signal amplifiers, such as erbium-doped fiber amplifiers (EDFA), is crucial. As a solution for EDFA, cladding pump has gained attention due to its low cost and high gain. This paper presents a cladding pump coupler (CP) based on double cladding passive optical fiber (DCF), fabricated using the fused taper technique, which supports the transmission of four modes: LP01, LP11, LP21, and LP02. The optical loss of this device is less than 0.3 dB, and it does not introduce new crosstalk in the transmission line, ensuring excellent mode beam quality. The fabricated device is fusion-spliced with a four-mode erbium-doped fiber (EDF), achieving very low splice loss. The EDFA based on this device exhibits outstanding performance. In the C-band, it can achieve an average gain greater than 21.56 dB, with an average differential mode gain (DMG) of 1.42 dB. When amplifying four modes simultaneously, the gain exceeds 19.21 dB, the DMG is less than 2.51 dB, and the noise figure (NF) is less than 7.348 dB. This is of great significance for enabling long-distance signal transmission in mode-division multiplexing systems.